2020
DOI: 10.1001/jamanetworkopen.2020.22349
|View full text |Cite
|
Sign up to set email alerts
|

Association of Prenatal Maternal Anxiety With Fetal Regional Brain Connectivity

Abstract: IMPORTANCEMaternal psychological distress during pregnancy is associated with adverse obstetric outcomes and neuropsychiatric deficits in children. Currently unavailable in vivo interrogation of fetal brain function could provide critical insights into the onset and timing of altered neurodevelopmental trajectories. OBJECTIVE To investigate the association between prenatal maternal stress, anxiety, and depression and in vivo fetal brain resting state functional connectivity. DESIGN, SETTING, AND PARTICIPANTS T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 95 publications
5
48
0
Order By: Relevance
“…In human research, investigation of the impact of maternal psychosocial distress during pregnancy on offspring brain development has been rapidly developing over the last decade and increasing evidence supports an association between maternal stress during pregnancy and offspring brain anatomy and connectivity in offspring. Maternal prepartum stress-associated variation in offspring brain phenotypes has been shown in fetuses ( De Asis-Cruz et al, 2020 ; van den Heuvel et al, 2021 ), neonates ( Dean et al, 2018 ; Lautarescu et al, 2020b ; Rifkin-Graboi et al, 2013 ; Scheinost et al, 2020 ), infants ( Qiu et al, 2015 ), children ( Davis et al, 2020 ; Donnici et al, 2021 ; Lebel et al, 2016 ), adolescents ( McQuaid et al, 2019 ) and young adults ( Favaro et al, 2015 ; Marečková et al, 2019 ) with phenotypes under investigation varying greatly including variation in brain anatomy as well as structural and functional brain connectivity. However, despite the conceptual underpinnings and empirical evidence in animals, there is little evidence in humans linking maternal psychosocial distress during pregnancy with offspring hippocampal and amygdalar volumetry to date.…”
Section: Introductionmentioning
confidence: 99%
“…In human research, investigation of the impact of maternal psychosocial distress during pregnancy on offspring brain development has been rapidly developing over the last decade and increasing evidence supports an association between maternal stress during pregnancy and offspring brain anatomy and connectivity in offspring. Maternal prepartum stress-associated variation in offspring brain phenotypes has been shown in fetuses ( De Asis-Cruz et al, 2020 ; van den Heuvel et al, 2021 ), neonates ( Dean et al, 2018 ; Lautarescu et al, 2020b ; Rifkin-Graboi et al, 2013 ; Scheinost et al, 2020 ), infants ( Qiu et al, 2015 ), children ( Davis et al, 2020 ; Donnici et al, 2021 ; Lebel et al, 2016 ), adolescents ( McQuaid et al, 2019 ) and young adults ( Favaro et al, 2015 ; Marečková et al, 2019 ) with phenotypes under investigation varying greatly including variation in brain anatomy as well as structural and functional brain connectivity. However, despite the conceptual underpinnings and empirical evidence in animals, there is little evidence in humans linking maternal psychosocial distress during pregnancy with offspring hippocampal and amygdalar volumetry to date.…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to the higher prevalence of medical conditions during pregnancy, that predispose to anxiety disorders ( 9 ). Furthermore, perinatal anxiety is associated with obstetric problems and can negatively affect offspring's emotional and cognitive development ( 10 19 ), possibly due also to connectivity changes shown in 32-week fetal brain ( 20 ). Taken together, these data suggest that anxiety in the perinatal period should be considered on its own.…”
Section: Introductionmentioning
confidence: 99%
“…18,64 We have shown that maternal psychological distress in otherwise healthy women revealed in utero impairments in foetal hippocampal growth and brain neurochemistry, while cerebral cortical maturation was accelerated with differing regional vulnerabilities for maternal stress, anxiety or depression. 29,65 Similarly, a recent study noted functional differences in foetal neurodevelopment, namely increased foetal reactivity in foetuses affected by maternal anxiety and decreased reactivity in those affected by maternal depression. 66…”
Section: Depression Anxiety and Mood Disordersmentioning
confidence: 90%
“…81 Furthermore, we have shown distinct differences in emerging brain networks of foetuses exposed to elevated levels of maternal stress compared to foetuses not exposed to maternal mental distress (Figure 6). 65 Ongoing research efforts are needed to further develop and refine normative trajectories of foetal brain structure, microstructure, metabolism and connectivity, in order to transform our ability to reliably F I G U R E 5 The metabolic trajectories of common cerebral metabolites in the foetal brain during the latter half of gestation. tCR (total Creatine, a marker of cellular energy stores); tNAA (total N-acetyl aspartate, a neuronal marker); tCh (total Choline, a marker of membrane synthesis and degradation), Scyllo (scyllo-inositol) and Ins (inositol, the inositols are osmolytes that serve as precursors to lipid synthesis) (Courtesy of NeuroImage) identify the compromised foetus.…”
Section: Assessment and Diagnosis: The Role Of Advanced Foetal Imagingmentioning
confidence: 99%